Comparative Analysis of Granola and Atlantic Potato Farming in Magetan Regency - Bayu Panggy Saputro; Sri Marwanti; Wiwit Rahayu (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
Potato is one of the vegetable commodities that are utilized by its tubers and have the potential to be developed, as is the case in Magetan Regency. This study aimed to analyze the costs, revenues, productivity, income, profits, efficiency, and profitability, as well as to compare the potato farming of Granola and Atlantic varieties. Location determination was done purposively with 100 respondents. The data used was quantitative data and the data collection techniques were observation, interviews, and documentation. The data were analyzed using Z distribution statistical tests at 95% confidence level (? 0.05). The results showed that the amount of granola potato farming costs was IDR 99,103,163 / ha / MT, revenue of IDR 158,310,720 / ha / MT, productivity of 22,590 kg / ha, income of IDR 101,857,730 / ha / MT, profit of Rp 59,207. 557 / ha / MT, efficiency 1.60 and profitability 0.60. While the cost of atlantic variety potato farming is IDR 97,332,514 / ha / MT, revenue is IDR 130,464,460 / ha / MT, productivity is 18,718 kg / ha, income is IDR 74,530,033 / ha / MT, profit is IDR 33,141,946 / ha / MT, efficiency 1.34 and profitability 0.34. There are differences in productivity, income, profits, efficiency, and profitability between the granola and atlantic varieties of potato farming. This research is expected to be an input for farmers to maximize the care of their farms so as to increase productivity, income, and profits of farmers.